Gender difference in arsenic biotransformation is an important metabolic basis for arsenic toxicity - Maihaba Muhetaer; Mei Yang; Rongxiang Xia; Yuanyan Lai; Jun Wu (BMC, 2022)
Abstract Background Arsenic metabolism enzymes can affect the toxic effects of arsenic. However, the effects of different genders on the metabolites and metabolic enzymes in liver arsenic metabolism is still unclear. This study analyzed the gender differences of various arsenic metabolites and metabolic enzymes and further explored the effects of gender differences on arsenic metabolism in liver tissues of rats. Methods Rats were treated with high/medium/low doses of iAs3+ or iAs5+. Liver pathological changes were observed with electron microscopy. The monomethyl aracid (MMA) and dimethyl aracid (DMA) was determined by high performance liquid chromatography-hydride generation atomic fluorescence spectroscopy. S-adenosylmethionine (SAM), arsenate respiratory reductase (ARR), nicotinamide adenine dinucleotide (NAD), purine nucleoside phosphorylase (PNP), pyruvate kinase (PK), and myeloperoxidase (MPO) SAM, ARR, NAD, PNP, PK, and MPO were determined by enzyme-linked immunoassay. RT-qPCR was used to determine Arsenic (+ 3 oxidation state) methyltransferase (AS3MT). Results The iAs3+ and iAs5+ at high doses induced pathological changes in the liver, such as increased heterochromatin and lipid droplets. Compared within the same group, MMA and DMA were statistically significant in iAs3 + high, iAs3 + medium and iAs5+ low dose groups (P < 0.05). MMA of male rats in iAs3+ high and medium groups was higher than that of female rats, and the DMA of male rats was lower than that of female rats. As3MT mRNA in the male iAs3+ high group was higher than that of females. Besides, compared between male and female, only in iAS3+ low dose, iAS3+ medium dose, iAS5+ low dose, and iAS5+ medium dose groups, there was significant difference in SAM level (P < 0.05). Compared within the same group, male rats had significantly higher PNP and ARR activities while lower PK activity than female rats (P < 0.05). Between the male and female groups, only the iAS3+ high dose and medium dose group had a statistically significant difference (P < 0.05). The NAD activity of females in iAS3+ high dose group was higher than that of males. Conclusion The gender differences in the arsenic metabolism enzymes may affect the biotransformation of arsenic, which may be one of the important mechanisms of arsenic toxicity of different sexes and different target organs.